Long-read sequencing reveals novel structural variation markers for key agronomic and quality traits of food-grade soybean - Wang, Zhibo; Belay, Kassaye; Paterson, Joe; Bewick, Patrick; Singer, William; Song, Qijian; Zhang, Bo; Li, Song (Frontiers in Plant Science, 2025)
Long read sequencing has been widely used to detect structure variations that are not captured by short read sequencing in plant genomic research. In this study, we described an analysis of whole genome re-sequencing of 29 soybean varieties using nanopore long-read sequencing. The compiled germplasm reflects diverse applications of food-grade soybeans, including soy milk and tofu production, as well as consumption of natto, sprout, and edamame (vegetable soybean). We have identified 365,497 structural variations in these newly re-sequenced genomes and found that the newly identified structural variations are associated with important agronomic traits. These traits include seed weight, flowering time, plant height, oleic acid content, methionine content, and Kunitz trypsin inhibitor content, all of which significantly impact soybean production, quality, and market value. Experimental validation supports the roles of predicted candidate genes and structural variants in these biological processes. Our research provides a new source for rapid marker discovery in soybean and other crop genomes using structural variation and whole genome sequencing.